Is conization once following by simple hysterectomy sufficient for all clinical stage IA1 cervical squamous cell carcinoma? - Jen-Ruei Chen; Mei-ling Chiu; Tao-Yuean Wang; Tzu-Chien Chen; Kuo-Gon Wang; Tsung-Hsien Su; Chih-Long Chang; Yuh-Cheng Yang; Kung-Liahng Wang (Elsevier, 2013)
Objective: The goal of this study is to assess the feasibility of simple extrafascial hysterectomy for patients with clinical stage IA1 cervical squamous cell carcinoma (SCC) after once conization regardless of any pathologic risk factor. Materials and Methods: All cases with T1a1, SCC lesion in their cervical cone specimen were retrospectively collected after chart and pathology review for the period between January 2002 and December 2009. All cases underwent subsequent hysterectomies within a month of diagnosis. Pathologic risk factors of conization, surgical scale of hysterectomy, residual lesion of the uterus, necessity of adjuvant radiation therapy, complications, and survival were analyzed in this study. Results: Eighty-one cases were identified from the registry. Most were managed by simple hysterectomy (SH; 60/81, 74%), and the remaining 21 cases underwent modified radical hysterectomy (MRH). All cases without any risk factors in their cone specimens demonstrated residual lesion ≤T1a1 in both SH and MRH groups, whereas those with existing risk factor were confirmed positive for residual lesions ≤T1a1 [SH, 95.8% (46/48) vs. MRH, 75% (15/20)]. Only two cases in the SH group received adjuvant radiation for residual lesions >T1a1. On the contrary, 15 cases in the MRH group can receive smaller scale surgery than MRH. All cases were recurrence-free without any permanent treatment-related complication by the end of the study. Conclusion: Extrafascial simple hysterectomy may be recommended for clinical T1a1 cervical SCC regardless of the pathologic risk factor.